Gas hydrate saturation at Site C0002, IODP Expeditions 314 and 315, in the Kumano Basin, Nankai trough. (7th April 2014) - Miyakawa, Ayumu; Saito, Saneatsu; Yamada, Yasuhiro; Tomaru, Hitoshi; Kinoshita, Masataka; Tsuji, Takeshi
Abstract The degree of gas hydrate saturation at Integrated Ocean Drilling Program (IODP) Site C0002 in the Kumano Basin, Nankai Trough, was estimated from logging‐while‐drilling logs and core samples obtained during IODP Expeditions 314 and 315. Sediment porosity data necessary for the calculation of saturation were obtained from both core samples and density logs. Two forms of the Archie equation ('quick‐look' and 'standard') were used to calculate gas hydrate saturation from two types of electrical resistivity log data (ring resistivity and bit resistivity), and a three‐phase Biot‐type equation was used to calculate gas hydrate saturation from P‐wave velocity log data. The gas hydrate saturation baseline calculated from both resistivity logs ranges from 0% to 35%, and that calculated from the P‐wave velocity log ranges from 0% to 30%. High levels of gas hydrate saturation (>60%) are present as spikes in the ring resistivity log and correspond to the presence of gas hydrate concentrations within sandy layers. At several depths, saturation values obtained from P‐wave velocity data are lower than those obtained from bit resistivity data; this discrepancy is related to the presence of free gas at these depths. Previous research has suggested that gas from deep levels in the Kumano Basin has migrated up‐dip towards the southern and seaward edge of the basin near Site C0002. The high saturation values and presence of free gas at site C0002 suggest that a large gas flux is flowing to the southern and seaward edge of the basin from a deeper and/or more landward part of the Kumano Basin, with the southern edge of the Kumano Basin (the location of site C0002) being the main area of fluid accumulation.